Cardiovascular diseases and osteoarthritis: general mechanisms of development, prospects for combined prevention and therapy - M. A. Kabalyk; V. A. Nevzorova (Кардиоваскулярная терапия и профилактика)
A critical analysis of the study’s results on the relationship of cardiovascular diseases and osteoarthritis is carried out. An assessment of the possibility of their combined prevention and treatment is given. The analysis of experimental, clinical and large-scale studies of recent years allows to put forward a well-founded concept, according to which the joint tissues are the target organ for a number of cardiovascular factors. Hypertension, hyperlipidemia, and obesity are among the most significant risk factors for degenerative joint diseases. In a number of studies, the primary role of these factors in the pathogenesis of osteoarthritis has been established, and therefore an attempt has been made to clinically classify cardiovascular comorbidity in osteoarthritis. Currently, there are reasons to believe that active non-pharmacological and pharmacological correction of cardiovascular factors can be used in the treatment of osteoarthritis.